2021
DOI: 10.1024/1662-9647/a000250
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Suicidal Ideation among Older Adults

Abstract: Abstract. This study examined the relationship of depression and life satisfaction with suicidal ideation among older Iranian adults. In this cross-sectional study, a total of 159 older adults in Tehran (73% community-residing, 60 years or older) participated. The data were gathered using the Beck Scale for Suicidal Ideation (BSSI), the Geriatric Depression Scale (GDS), and the Life Satisfaction Index-Z (LSIZ). According to the results, depression and life satisfaction are significantly related to suicidal ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…An assessment of the convergent and divergent validity of the scale showed that the total P-RFL-OA score was negatively associated with suicide risk factors, including suicidal ideation/thoughts and depression, but positively associated with protective factors, such as life satisfaction and quality of life in older adults. These findings confirmed the importance of suicide risk assessment in old age with a focus on negative variables such as depression (Almeida et al, 2012;Rossom et al, 2019) and positive variables such as life satisfaction and quality of life (Foroughan et al, 2021;Kwon & Kim, 2012). Many studies (Heisel et al, 2016;Marty et al, 2010;Miller et al, 2001;Segal et al, 2015) found a significant and positive relationship between depression as a risk factor for suicide as well as a significant and negative relationship with life satisfaction, religiosity, child-related concerns, perceived social support, and self-rated health as flexibility and protective variables with suicide in older adults.…”
Section: Discussionsupporting
confidence: 71%
“…An assessment of the convergent and divergent validity of the scale showed that the total P-RFL-OA score was negatively associated with suicide risk factors, including suicidal ideation/thoughts and depression, but positively associated with protective factors, such as life satisfaction and quality of life in older adults. These findings confirmed the importance of suicide risk assessment in old age with a focus on negative variables such as depression (Almeida et al, 2012;Rossom et al, 2019) and positive variables such as life satisfaction and quality of life (Foroughan et al, 2021;Kwon & Kim, 2012). Many studies (Heisel et al, 2016;Marty et al, 2010;Miller et al, 2001;Segal et al, 2015) found a significant and positive relationship between depression as a risk factor for suicide as well as a significant and negative relationship with life satisfaction, religiosity, child-related concerns, perceived social support, and self-rated health as flexibility and protective variables with suicide in older adults.…”
Section: Discussionsupporting
confidence: 71%
“…Old age may limit physical and mental abilities, affect social and economic activities, and be accompanied by chronic disorders [ 1 ]. These characteristics may threaten older adults’ quality of life and possibly trigger depression and even suicidal ideation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aging is a continuous process and leads to a gradual decrease in physiological functions, which in turn reduces the functional capacity of the person ( Foroughan et al, 2021 ). Aging has been a major issue for experts, policymakers, and even the general public in recent years.…”
Section: Introductionmentioning
confidence: 99%